What are the impacts of reindeer/caribou (Rangifer tarandus L.) on arctic and alpine vegetation? A systematic review protocol - Bernes, Claes; Bråthen, Kari Anne; Forbes, Bruce C; Hofgaard, Annika; Moen, Jon; Speed, James DM (Environmental evidence, 2013)
Background Reindeer and caribou (both belonging to the species Rangifer tarandus L.) are among the most important large herbivores in Eurasia's and North America's arctic, alpine and boreal zones. In Sweden, the impact of reindeer grazing on arctic and alpine vegetation has recently been re-evaluated. In the 1990s, records of grazing-related vegetation degradation helped to form a widespread perception that some mountain areas were overgrazed. However, later analyses have shown no evidence of large-scale overutilisation of reindeer ranges in the Swedish mountains. The present-day consensus is that overgrazing has been temporary and local, and that it rarely has caused permanent damage, but it is imperative to examine the scientific support for these views. Moreover, the Swedish Parliament has adopted an environmental quality objective according to which it is essential to preserve 'a mountain landscape characterised by grazing'. No details have been given on how this goal is to be interpreted, which is another reason why the significance of reindeer grazing for arctic/alpine vegetation needs to be assessed. This protocol presents the methodology that will be used in a systematic review of the impact of reindeer herbivory in arctic and alpine ecosystems. The focus will be on Fennoscandia, but data from other parts of the range of R. tarandus will be used when deemed appropriate. Methods The review will be based on primary field studies that compare vegetation subject to different degrees of reindeer/caribou herbivory (including grazing and browsing as well as trampling). Such comparisons can be either temporal, spatial or both. The review will cover impacts of herbivory in arctic, subarctic, alpine and subalpine areas (including the forest-tundra ecotone) across the range of R. tarandus, but not in boreal forests. Relevant aspects of vegetation include cover (abundance), biomass, diversity (e.g. species richness), structure, composition (including functional groups) and productivity. Keywords: Reindeer, Caribou, Rangifer tarandus, Herbivory, Grazing, Browsing, Vegetation, Alpine, Arctic, Tundra